TARGET MOLEKULER UNTUK DESAIN PENGOBATAN PRURITUS NOKTURNAL PADA PASIEN SKABIES: Molecular Target for Treatment Design of Nocturnal Pruritus in Scabies Patients - Reqgi First Trasia; Samsul Mustofa; Endang Purwaningsih; Sri Wahyu Herlinawati (Forind Press, 2024)
Pruritus is one of the factors that contributes to reduced quality of life in patients with scabies, along with disease severity and sleep disturbances. So far not much is known about the molecular targets in scabies treatment. The aim of this article is to examine the potential of molecular targets for the design of treatment for nocturnal pruritus as the main symptom of scabies. Evidence in various literature correlates the incidence of scabies with a number of targets found in the skin, such as NK1R, JAK, TRPV1 and TRPA1 channels, because the expression of these receptors is very high in the skin lesions of patients suffering from nocturnal pruritus, when compared with skin that does not have lesions. . Results from comparing three molecular targets and considering the development of new therapeutic strategies with structure-based design, NK1R seems to be the most promising due to recent findings of its crystallographic structure.